PRODUCTIVITY OF MANGOLD VARIETY SAMPLES IN UZBEKISTAN - Yunusov O. B.; Akramov U. I.; Pirmetova S. A. (Modern American Journals, 2025)
In the soil and climatic conditions of Uzbekistan, among the mangold variety samples, the highest leaf yield was observed in the Raduga (35.3 t/ha), Brazilskiy (34.4 t/ha), and Krasavitsa (33.7 t/ha) varieties, while the lowest leaf yield was observed in the Rubin (22.3 t/ha), Aliy (22.3 t/ha), Zeleniy (21.1 t/ha), and Lukullus (14.5 t/ha) varieties.
Keywords: Mangold, variety samples, plant height, number of leaves, leaf length, leaf width, leaf surface area, leaf weight per plant, leaf yield.